An efficient protocol for particle bombardment-mediated transformation of Centella asiatica callus - Lai, Kok Song; Abdullah, Puad; Yusoff, Khatijah; Mahmood, Maziah (Springer-Verlag, 2011)
In this study, we report an optimization of particle bombardment transformation system for Centella asiatica callus. A total of eight parameters affecting the genetic transformation system were optimized using the synthetic green fluorescent protein (sGFP) as a reporter driven by the CaMV 35S promoter. The results indicated that DNA delivery conditions of 9-cm target distance, 1,100 psi helium pressure, 1.0 μm gold particles size, 27 mmHg chamber vacuum pressure, 2 times number of bombardment, spermidine as precipitation agent, 60 h post-bombardment incubation time and 2 μg plasmid DNA concentration were optimal for C. asiatica callus transformation. The expression of sGFP was monitored using fluorescence microscope and further confirmed using RT-PCR. This optimized genetic transformation system is applicable for rapid transient gene analysis and transgenic C. asiatica production.